“Rescue Our Family From a Living Death:” Refugee Professors and the Canadian Society for the Protection of Science and Learning at the University of Toronto, 1935-1946 - Stortz, Paul (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2003)
AbstractThroughout the 1930s into the early 1940s, the University of Toronto was inundated with desperate letters for succor from European professors who were persecuted under Nazism. Many of the stories in these appeals outlined life and death situations. The university responded by hiring some of these professors, but vigorous debate erupted with the establishment of the Canadian Society for the Protection of Science of Learning in 1939. The Toronto Society, the most influential of the other, more smaller Societies in Canada, was struck as an organization to place refugee professors in Canadian universities. It is an excellent case study in analyzing the socio-economic, political, and intellectual responses to a humanitarian disaster. The Society brought to the fore the spectre of racism and anti-Semitism in various academic and social communities in Canada, and further supported the historical argument that the Immigration Branch in Ottawa had particular, oppositional agendas in dealing with refugees of particular ethnicities and cultures. The Society highlighted the tensions of altruism and practicality, accommodation versus discrimination, and intellectualism overwhelmed in a oft-times hostile anti-intellectual and defensive society. The rapid failure of the Society demonstrated that strategies used by Canadian professors to offer safe harbour for their fleeing European counterparts were far too powerless in the fight against entrenched beliefs and conformist understandings in higher education and society as a whole.